PENGUATAN KANTIN SEHAT RAMAH LINGKUNGAN SDN KROGOWANAN MELALUI EDUKASI LEAFLET DAN VOUCHER MAKANAN - Galih Istiningsih; Shofia Wulan Nis Mara; Asma’ulkhusna; Siska Yogi Septiana; Auretha Diva Nur Ferasari; Annisa Dian Salsabila (Open Edutech Indonesia, 2024)
The permanent canteen facilities and management at SDN Krogowanan are crucial elements in promoting healthy canteen practices at the school. However, efforts to provide healthy and safe snack foods are still lacking. There is a need to enhance the knowledge of canteen vendors regarding food hygiene and sanitation standards to ensure the availability of safe and healthy food. Additionally, students also need to be provided with adequate understanding to make wise choices when selecting snack foods. In order to improve the implementation of a healthy canteen at SDN Krogowanan, community engagement activities were conducted, including educational sessions for third and fourth-grade students as well as canteen vendors. The aim of this program is to enhance students' knowledge of selecting healthy snack foods and to provide canteen vendors with knowledge on offering healthier and safer snack food options. Evaluation was conducted by comparing pre-test and post-test results to assess students' knowledge improvement, which showed statistically significant increases. Meanwhile, canteen vendor education was facilitated through a WhatsApp Group, demonstrating positive outcomes in terms of implementing food hygiene and selecting healthier food options. However, there have been no significant changes observed in the types of food sold, the behavior of canteen vendors, or canteen facilities after two months of educational intervention. Nevertheless, the nutrition education program successfully increased students' and canteen vendors' knowledge about selecting safe and healthy snack foods. However, this increase is not yet sufficient to achieve a fully healthy canteen implementation at the school.